Penerapan Zahir Accounting Versi 6.0 Dalam Pengelolaan Data Keuangan PT Pasifik Mitra Lestari - Sulistiyah, Sulistiyah; Farabi, Nur Ali (LPPM Universitas Bina Sarana Informatika, 2024)
In today's technological developments, it has quite a big influence on the business world. A computerized system will be better than a manual record system. So that it runs more accurately and efficiently. It is a requirement needed by business sectors, from small businesses, medium companies to large companies, so that financial data processing is fast, accurate and systematic. Therefore, the author conducted research at PT Pasifik Mitra Lestari with the aim of managing financial accounting data with a computerized system, because PT. Pasifik Mitra Lestari is still manual. The author uses Zahir accounting software version 6.0 for all transaction activities and financial reports at PT. Pasifik Mitra Lestari so that financial reporting results become more accurate. The implementation of Zahir Accounting Version 6.0 will be a solution to support the activities of PT Pasifik Mitra Lestari. Zahir accounting software version 6.0 is easy to carry out work in processing financial data reports